2020
DOI: 10.18805/lr-536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Boron Priming on the Antioxidant Ability of Alfalfa Seeds

Abstract: This experiment was designed to determine the relationship between the antioxidant capacity and the vigour of alfalfa seeds during boron priming. Alfalfa seeds were primed with 1.8 % (W/V) concentration of borax solution for 0, 3, 6, 12 and 24 h at 20°C. The results showed that the vigour of alfalfa seeds declined with the extension of priming time, which was closely related to the accumulation of hydrogen peroxide and malonaldehyde contents and the decrease of superoxide dismutase, catalase and peroxidase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Low concentration of boron had positive effects on meristematic growth (Khan et al, 2006) and SVI (Table 5, Farooq, 2011;Xia et al, 2019). The SVI frequently reflected the establishment ability of the seedling during plant growth (Xia et al, 2020) In this experiment SL was reduced by 52.50 % and RL decreased by 65.71 % (Table 5). The main reason for the reduction in RL is that higher doses of boron inhibit root growth (Habtamu et al, 2014), primarily by limiting cell protraction and cell division (Brown et al, 2002).…”
Section: Resultsmentioning
confidence: 67%
“…Low concentration of boron had positive effects on meristematic growth (Khan et al, 2006) and SVI (Table 5, Farooq, 2011;Xia et al, 2019). The SVI frequently reflected the establishment ability of the seedling during plant growth (Xia et al, 2020) In this experiment SL was reduced by 52.50 % and RL decreased by 65.71 % (Table 5). The main reason for the reduction in RL is that higher doses of boron inhibit root growth (Habtamu et al, 2014), primarily by limiting cell protraction and cell division (Brown et al, 2002).…”
Section: Resultsmentioning
confidence: 67%
“…Chemical priming is the soaking of seeds in various types of chemicals which may be natural or synthetic in origin like choline, chitosan, ethanol, zinc sulphate, copper sulphate, potassium di hydrate phosphate, selenium which enhances crop growth and induce resistance to various abiotic stresses (Maurya et al, 2020). Primimg using boron enhanced the antioxidant activity in alfalfa seeds (Xia et al, 2020).…”
Section: Chemical Primingmentioning
confidence: 97%
“…When ROS are overproduced under stress conditions, they can cause cell damage (Xia et al, 2020). The high activity of SOD, CAT during the germination phase (490, 784, 980 mM exogenous H 2 O 2 ), suggested that hydrogen peroxideinduced strong defense activity during the oxidation pathway removed high concentrations of H 2 O 2 and inhibits accumulation of ROS and protect plants from lipid peroxidation (Wang et al, 2009).…”
Section: Treatments Treatmentsmentioning
confidence: 99%